Design and performance comparison of a novel high Q coaxial resonator filter and compact waveguide filter for millimeter wave payload applications. Issue 8 (9th April 2019) - Dad, Vineet K.; Gupta, Sanjeev
Abstract: A novel high‐performance high Q filter with ultra‐wide spurious‐free stopband and thermally stable performance is introduced using higher order mode of the coaxial resonator. The 7‐pole Chebyshev and a 5‐pole cross‐coupled filter are designed at Ka‐band to validate the concept. A compact cross‐coupled waveguide filter is introduced with a different approach to realize cross‐coupling makes the filter compact. The coaxial resonator and waveguide resonator filter have the same configuration, and their performances are compared at ambient and over the temperature. The high power analysis is done for both these filters to find their power handling capability. The high power performance of the coaxial resonator filter is superior, and it can handle 45.525 kW peak power. This filter is suitable to be used as pre‐select filter in millimeter wave payloads as well as for high power filtering applications.